ENLIGHTENMENT: THE PROCESS OF DISMANTLING GENDER INEQUALITY THROUGH EDUCATION - Lourembam, Dhanamanjuri; Mairembam, Kalpana; Athiphro, Ashihrii (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Enlightenment philosophy provides the knowledge that human beings are different from other beings because we uphold on reasons rather than on any other aspects. It has been again further analysed that human beings are already inherently enlightened but have not realized it yet .This realization can only happen when human beings have been given accessed to the light of Education. The present global society is a technology savvy world where development can be seen and observed in every sector and is still moving uber fast and strong all around. Women’s participation in all sectors of development is a truism that needs no debate .In Spite of all the contributions women are providing, still,it is again a reality that great disparities between men and women in all aspects can be seen everywhere. Many are of the opinion that gender sensitization in the education sector is the missing link to completely eradicate this ill from making the world a harmonious one to facilitate a necessary condition for the survival and development of humankind.